Cardiorespiratory Response to Exercise before and after Pulmonary Valve Replacement in Patients with Repaired Tetralogy of Fallot: A Retrospective Study and Systematic Review of the Literature. (4th August 2014) - Sabate Rotes, Anna; Johnson, Jonathan N.; Burkhart, Harold M.; Eidem, Benjamin W.; Allison, Thomas G.; Driscoll, David J.
Abstract Objective To describe and analyze the cardiopulmonary responses to exercise for patients with repaired tetralogy of Fallot (TOF) before and after pulmonary valve replacement (PVR) and compare our results with those in the literature. Methods Between 1973 and 2012, 278 patients had a first‐time PVR after TOF repair. During their evaluations, 76 patients (27%) had exercise testing before PVR, and 63 (23%) had at least one test after PVR. There were 17 patients (average age at surgery 40 ± 14 years, 65% female) with both pre‐ and postoperative testing within 36 months of surgery. We then combined our results with previously reported studies for meta‐analysis. Results Patients who had exercise testing before PVR were older compared with those who did not have testing performed (37 ± 13 vs. 30 ± 17 years, P < .001). Preoperatively, patients achieved a peak heart rate of 153 ± 28 bpm and a peak VO2 of 21.5 ± 7.2 mL/kg/min (61 ± 15% of expected). Postoperatively, they achieved a peak heart rate of 156 ± 25 bpm and a peak VO2 of 23.3 ± 6.5 mL/kg/min (67 ± 15% of expected). Paired analysis demonstrated a significant increase in peak VO2 percentage (P = .04) but not for absolute VO2 measurements (mL/kg/min). We identified six published studies with similar usable data. Combining all seven data sets for meta‐analysis, there was no significant change in peak VO2 following PVR (P = .2). Conclusions Patients with repaired TOF have an abnormally low aerobic capacity at the time of PVR. We appreciated a modest improvement in percentage of predicted peak VO2 after PVR; however, meta‐analysis of the available literature did not demonstrate an appreciable difference in aerobic capacity following PVR.